2014
DOI: 10.1186/1471-2334-14-295
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of childhood tuberculosis in the Netherlands: still room for prevention

Abstract: BackgroundThe occurrence of tuberculosis (TB) among children has long been neglected as a public health concern. However, any child with TB is a sentinel event indicating recent transmission. Vaccination, early case finding and treatment of those latently infected with TB can prevent cases, severe morbidity and unnecessary death.MethodThe objective of the study was to describe the occurrence of TB events among children in the Netherlands which may be avoided through preventive measures. For this purpose we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…This study provides original, comprehensive and recent data on the epidemiological and clinical characteristics of TB in children in Australia. Paediatric cases of TB accounted for 5% of the total national TB case load, a finding similar to those of recent reports from other low‐incidence settings 15 . ‐ 17 National rates of TB in children in Australia have not changed markedly over the past 10 years, consistent with the stable rate for the overall population 18…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study provides original, comprehensive and recent data on the epidemiological and clinical characteristics of TB in children in Australia. Paediatric cases of TB accounted for 5% of the total national TB case load, a finding similar to those of recent reports from other low‐incidence settings 15 . ‐ 17 National rates of TB in children in Australia have not changed markedly over the past 10 years, consistent with the stable rate for the overall population 18…”
Section: Discussionsupporting
confidence: 85%
“…In most cases (56%), the reported country of birth was outside Australia, and this proportion was higher than the corresponding figures for New Zealand, the United States and western Europe, where 26%–31% of patients with TB were born outside the respective country 16 , 17 , 19 . The notification rate of 9.57 per 100 000 overseas‐born children per year is lower than the rate of 35–37 per 100 000 overseas‐born children reported for the United Kingdom (1999–2006) and the Netherlands (1993–2012) 15 , 20 . This difference may reflect the fact that there was no pre‐migration screening in those countries during the reported periods, so that all cases were detected and notified after arrival.…”
Section: Discussionmentioning
confidence: 57%
“…12,15,25 In the USA surveillance dataset, which provided the vast majority of the HIV-stratified data, CFRs were higher for HIV-infected children than HIV-uninfected children (Table 3). We were unable to extract data about HIV-infected children’s immune status or whether they were receiving antiretroviral therapy, but stratifying the USA surveillance data into time periods before and after the widespread availability of highly active antiretroviral therapy suggests a protective effect 15 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…A prospective study showed that only 53% of patients completed the therapy [26]. Erkens et al [27] showed that of 1,049 children with LTBI started on LTBI treatment in 2005-2012, and 90% completed the treatment. In our study, the LTBI treatment completion rate was 95%.…”
Section: Discussionmentioning
confidence: 99%